Unraveling boron-organic template interactions in [B, Al]-ZSM-5 zeolite using solid-state NMR spectroscopy - Yongxiang Wang; Shuangqin Zeng; Pengfei Wang; Mingji Zheng; Weidong Huang; Yueying Chu; Ningdong Feng; Guodong Qi; Qiang Wang; Jun Xu; Feng Deng (Magnetic Resonance Letters)
Organic structure directing agents (OSDAs), such as tetrapropylammonium (TPA) cations, serve as crucial templates for the formation of zeolite frameworks. These organic molecules interact with inorganic species, guiding the assembly of the zeolite structure. In this study, we investigate the complex interplay between boron species and TPA cations during the crystallization of [B, Al]-ZSM-5 zeolites. Two-dimensional(2D) 11B-{1H} cross-polarization heteronuclear correlation (CP-HECTOR) NMR experiments elucidate distinct interactions between two boron species, B(IV)-1 and B(IV)-2, and the propyl chain of the TPAs. Amorphous B(IV)-1 species exhibit a strong preference for proximity to the nitrogen cation center of the OSDAs, while framework B(IV)-2 species engage with components situated at greater distances from the cation center. Moreover, 13C-{11B} symmetry-based resonance-echo saturation-pulse double-resonance (S-RESPDOR) experiments revealed that framework boron species preferentially occupy the straight channels of the MFI structure, as evidenced by their interaction with specific methyl groups on the TPA molecules. This observation provides valuable insights into the crystallization mechanism of boron-based zeolites, suggesting that the conformation and orientation of the OSDA molecules play a critical role in determining the location of boron atoms within the zeolite framework.